2017
DOI: 10.1128/mbio.02134-16
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Zika Virus Stability and Developing a Chimeric Vaccine through Functional Analysis

Abstract: Compared with other flaviviruses, Zika virus (ZIKV) is uniquely associated with congenital diseases in pregnant women. One recent study reported that (i) ZIKV has higher thermostability than dengue virus (DENV [a flavivirus closely related to ZIKV]), which might contribute to the disease outcome; (ii) the higher thermostability of ZIKV could arise from an extended loop structure in domain III of the viral envelope (E) protein and an extra hydrogen-bond interaction between E molecules (V. A. Kostyuchenko, E. X.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 28 publications
(49 reference statements)
3
53
1
Order By: Relevance
“…Day 6-cultured DCs were infected with ZIKV at an MOI of 1. At day 1, 3, and 4 p.i., culture fluids were measured for infectious virus using plaque assays on Vero cells (Xie et al, 2017). The infected cells were extracted for total intracellular RNA using Trizol (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…Day 6-cultured DCs were infected with ZIKV at an MOI of 1. At day 1, 3, and 4 p.i., culture fluids were measured for infectious virus using plaque assays on Vero cells (Xie et al, 2017). The infected cells were extracted for total intracellular RNA using Trizol (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…Among these candidates, subunit and inactivated vaccines have shown efficacy in both mice and NHPs, and several of these candidates have already advanced to phase 1-II clinical evaluation in humans (Barouch et al, 2017). Chimeric virus and live-attenuated vaccines have shown murine efficacy (Xie et al, 2017; Shan, 2017), but their efficacies in NHPs remains to be reported. These promising preclinical results are not surprising because similar approaches have been successful for development for other flavivirus vaccines.…”
Section: Current Status Of Vaccine Development (Chao Shan and Pei-mentioning
confidence: 99%
“…To support the feasibility of this approach, Xie et al recently reported a chimeric DENV-2 containing the ZIKV prM-E genes that fully protected against WT ZIKV challenge in the A129 mouse model; reciprocally, a chimeric ZIKV containing the DENV-2 prM-E genes completely protected WT DENV-2 challenge (Xie et al, 2017). Along the same lines, Stephen Whitehead and colleagues are currently developing such chimeric vaccines using the 3′UTR deletion DENV vaccine backbones (personal communications).…”
Section: Current Status Of Vaccine Development (Chao Shan and Pei-mentioning
confidence: 99%
“…Studies using neural progenitor cells (NPCs) and mice further show that ZIKV may disrupt the development of and induce the death in NPCs, which leads to microcephaly (Dang et al, 2016; Li et al, 2016). Currently, little is known about ZIKV pathogenesis and there is no approved antiviral therapy or licensed human vaccines, though several groups have identified potential antiviral targets or candidate vaccines in experimental models (Abbink et al, 2016; Barrows et al, 2016; Richner et al, 2017; Xie et al, 2017; Xu et al, 2016). …”
Section: Introductionmentioning
confidence: 99%